Cell‐intrinsic reprogramming capability: gain or loss of pluripotency in germ cells. (19th June 2012) - Imamura, Masanori; Lin, Zachary Yu‐Ching; Okano, Hideyuki
Abstract: In multicellular organisms, germ cells are an extremely specialized cell type with the vital function of transmitting genetic information across generations. In this respect, they are responsible for the perpetuity of species, and are separated from somatic lineages at each generation. Interestingly, in the past two decades research has shown that germ cells have the potential to proceed along two distinct pathways: gametogenesis or pluripotency. Unequivocally, the primary role of germ cells is to produce gametes, the sperm or oocyte, to produce offspring. However, under specific conditions germ cells can become pluripotent, as shown by teratoma formation in vivo or cell culture‐induced reprogramming in vitro. This phenomenon seems to be a general propensity of germ cells, irrespective of developmental phase. Recent attempts at cellular reprogramming have resulted in the generation of induced pluripotent stem cells (iPSCs). In iPSCs, the intracellular molecular networks instructing pluripotency have been activated and override the exclusively somatic cell programs that existed. Because the generation of iPSCs is highly artificial and depends on gene transduction, whether the resulting machinery reflects any physiological cell‐intrinsic programs is open to question. In contrast, germ cells can spontaneously shift their fate to pluripotency during in‐vitro culture. Here, we review the two fates of germ cells, i.e., differentiation and reprogramming. Understanding the molecular mechanisms regulating differentiation versus reprogramming would provide invaluable insight into understanding the mechanisms of cellular reprogramming that generate iPSCs.